Рассказ А.П. Чехова «Студент» и рефлексия венгерского писателя Деже Костоланьи в очерке «Tavaszi gyász» («Весенний траур») - Регеци, Ильдико (SlavVaria, 2023)
Chekhov’s Short Story “The Student” and Dezső Kosztolányi’s Reflection: the Feuilleton Titled “Spring Mourning”. Dezső Kosztolányi’s feuilleton titled Spring Mourning, written in 1909, undertakes to evoke a decisive feeling from the childhood of the writer: the atmosphere of sadness that pervades Good Friday. This piece of writing considers a childhood incident as an experience determining the adult personality, and the artistically drawn images in it come into contact with A.P. Chekhov’s 1894 short story “The Student.” Kosztolányi’s life experience depicted in the journalistic text becomes interpretable within the recipient’s horizon of the Russian writer’s short prose fiction but, at the same time, under the influence of Chekhov’s poetics and through the surplus of artistic textualization, the piece of writing not only concretizes the former incident, but also expands it and transforms it into a universal experience, opening the way for experiencing the mystery of Easter by an individual.